Challenges start-up founders face between the ideation and first round of investment phases: a study on the discrepancy between narrower and broader perspectives in the Portuguese ecosystem - Diniz, João Pedro Lopes Serrado Coelho (2020)
The research projectpresented belowdelves into the largest andmost significant challenges thatstart-up founders face between their ideationand first round of investment phases.Throughliterature review on the subject matter it is postulated that these are mostly related to lengthylegal procedures,a lack of a science-basedapproach to building a business, andtensions betweenpartnersand investorsof the start-ups. However, interviews reveal that the issues most present in founders’minds are those related to recruitment, decision-times, and clarity in procedures.